Nurses' narratives of moral identity: Making a difference and reciprocal holding. (May 2018) - Peter, Elizabeth; Simmonds, Anne; Liaschenko, Joan
Background: Explicating nurses' moral identities is important given the powerful influence moral identity has on the capacity to exercise moral agency. Research objectives: The purpose of this study was to explore how nurses narrate their moral identity through their understanding of their work. An additional purpose was to understand how these moral identities are held in the social space that nurses occupy. Research design: The Registered Nurse Journal, a bimonthly publication of the Registered Nurses' Association of Ontario, Canada, features a regular column entitled, 'In the End … What Nursing Means to Me …' These short narratives generally include a story of an important moment in the careers of the authors that defined their identities as nurses. All 29 narratives published before June 2015 were analysed using a critical narrative approach, informed by the work of Margaret Urban Walker and Hilde Lindemann, to identify a typology of moral identity. Ethical considerations: Ethics approval was not required because the narratives are publicly available. Findings: Two narrative types were identified that represent the moral identities of nurses as expressed through their work: (1) making a difference in the lives of individuals and communities and (2) holding the identities of vulnerable individuals. Discussion: Nurses' moral identities became evident when they could see improvement in the health of patients or communities or when they could maintain the identity of their patients despite the disruptive forces of illness and hospitalization. In reciprocal fashion, the responses of their patients, including expressions of gratitude, served to hold the moral identities of these nurses. Conclusion: Ultimately, the sustainability of nurses' moral identities may be dependent on the recognition of their own needs for professional satisfaction and care in ways that go beyond the kind of acknowledgement that patients can offer.